1141 CARDIAC METASTASIS. (15th December 2022) - Ricci, Giulia; Vannelli, Andrea; Onorato, Federica; Morgagni, Riccardo
Abstract: Introduction: in medical literature, studies on cardiac metastases are few and discordant and their actual incidence is underestimated. Autoptic examination shows evidence of cardiac metastases in about 9% of all the patients affected by malignant tumor. Each malignant tumor can metastasize to the heart (incidence varying from 2.3% to 18.3%); nevertheless, formation of cardiac metastases is more frequently associated with primitive neoplasms such as pleural mesothelioma (48.4%), melanoma (27.8%), adenocarcinoma as well as lung and kidney carcinomas. Clinical case: patient aged 66, former smoker, no further cardiovascular disease risk factors, no occurrences of heart disease in his past medical history. In 2008 surgical excision of melanoma skin cancer, negative sentinel lymph node. In 2014 cancer relapse, final cycle of chemotherapy treatment completed in July. In October 2014 evidence of liver and adrenal gland metastases. In November 2014 evidence of bone metastases. As the CT scan showed evidence of pleural and pericardial effusion, the patient was requested to undergo cardiac examination and an echocardiogram test in preparation for further chemotherapy treatment. During the medical examination the patient presented with symptoms of marked asthenia, dyspnea under moderate effort (NYHA II), palpitations. BP: 100/60 mmHg. ECG: low voltages, sinus tachycardia, incomplete RBBB, inverted T waves in V1 – V4, III. Home Therapy: Furosemide 25 mg, Cortisone 25 mg, Tramadolo Cloridrato 50 mg, Albumina. The findings of the echocardiogram test showed: enlarged and hyperkinetic left ventricle, abundant circumferential pericardial effusion measuring up to 2, 3 cm. Evidence of hyperechogenic areas in the epicardium, myocardium and at the level of mitral valve flaps (figure 1 and 2). In December 2014 hospital admission due to worsening of clinical symptoms, onset of ascites, hyperpotassemia, anemization (Hb 8.6g/dL). During the 72 hours following hospitalisation: STEMI, acute kidney failure, respiratory failure, metabolic acidosis, death. The autoptic examination showed evidence of undifferentiated large cell neoplasm with formation of metastases in the myocardium, mitral valve apparatus and coronary tree. Conclusions: echocardiography should always be included in the clinical examinations which patients affected by neoplasm are required to undergo. Serial evaluations allow to identify the occurrence of pericardial effusion and/or heart involvement even in the absence of clinical suspicion. Identifying such anomalies may have important therapeutic implications.